The Technological and Economic Future of Nuclear Power - Khalil ur Rahman (CISS Insight Journal, 2025)
This book is edited by Reinhard Haas, Lutz Mez, and Amela Ajanovic, with contributions from various researchers and analysts in the areas of the economics of nuclear power, the legal and political aspects of sustainable energy, climate policies, and technical challenges. The book provides a comprehensive discussion and analysis of the technical and economic factors hindering the renaissance of nuclear power. It is divided into seven themes, covering a range of aspects that include nuclear power history, economics, legislation, technical issues, nuclear waste and proliferation, major accidents, and alternatives.